Unmapping the 21st century : between networks and the state - Michelsen, Nicholas; Bolt, Neville (Bristol University Press, 2022)
Drawing on post-structural political theory, this book explores two concepts used to make sense of our disturbed reality: the state and the network. It argues that, in order to better understand today's world, we must pull apart the familiar lines of our maps to find new insights and opportunities for a better future.